G367(P) Head injury and a&e attendance in children – scottish population cohort. (24th May 2017) - Bashir, S; Dickson, L Chatterton; Davies, M; Easter, J; Gisbey, J; Jones, R; Linley-Adams, S; Yu, T; Leonard, P; Shetty, J
Abstract : Aims: A significant proportion of A and E attendances consist of paediatric head injuries (HI) and can lead to neurodisability if severe. We describe the epidemiological background of all children attending secondary care and their outcome. We studied the links between epidemiological factors, clinical features and socio- economic status to potentially recommend public health interventions. Methods: We collected a series of data for all children (£12 years) attending a Scottish secondary care department for the year of 2015. Data included age, gender, time, month, source of referral, triage category, clinical outcome and postcode. Scottish Index of Multiple Deprivation (SIMD) was obtained using postcode data. Case notes were reviewed to look at the clinical outcome. Results: A total of 2812 children (M>F) attended A and E with HI (4% of all paediatric attendance). Only 3.5% were admitted to hospital of which 76% were for observation only, 23% required neuroimaging and 1% suffered traumatic brain injury. Median age was 3 years with an increased proportion of infants and preschool children compared with school age children. Majority presented in the evening with peak numbers in May and September. The majority of patients of all age groups were triaged into categories 3, 4 or 7 of the Manchester Triage Categories, which was similar to the triaging pattern for the rest of A and E attenders. There were a higher number of attendees from the least deprived areas (SIMD decile 10 than any other SIMD decile). However we found no link between SIMD and severity of injury and the hospital is located in an affluent area. There did not seem to be a link with referral source or SIMD grouping and triage category used. Conclusions: We analysed population based epidemiological data of children attending secondary care with HI. During this study period the majority of children had minor HI. We found an increased attendance from younger age groups and higher socioe- conomic status. There is no correlation to the clinical outcome to any of the factors studied. We believe these epidemiological data are helpful in planning public health interventions to reduce head injury. These data are also helpful in secondary care resource planning.